Breaking Barriers and Overcoming the Odds Confronting Intergenerational Communication Barriers to Adolescent Sexuality Education in Southwestern, Nigeria - Monisola, Ola Tolulope (Richtmann Publishing, 2012)
There is a growing need to effectively address the sexual and reproductive health needs of adolescents in Nigeria. Researchshows a pattern of adolescent sexual behavior indicating early sexual debut and a prevalence of premarital sex. The traditional lack ofinterest in discussing sexuality at home, schools and churches creates a problem in teacher-student/ parent-child communication andthis has affected sexuality and sexuality education adversely overcoming communication barriers to sexuality education is critical to thewell-being of millions of adolescent in Nigeria today since communication barriers complicate the delivery of sexuality education both athome, churches and in schools. This paper therefore examines the dearth and ease in effectively communicating the idea of sexualitythrough the family, church and school which play major roles in socialization and ultimately, the education process. The paper concludesby discussing the social, health and educational implications of sexuality education in Nigeria.